2014
DOI: 10.1289/ehp.1307177
|View full text |Cite
|
Sign up to set email alerts
|

The Navigation Guide—Evidence-Based Medicine Meets Environmental Health: Systematic Review of Nonhuman Evidence for PFOA Effects on Fetal Growth

Abstract: Background: In contrast to current methods of expert-based narrative review, the Navigation Guide is a systematic and transparent method for synthesizing environmental health research from multiple evidence streams. The Navigation Guide was developed to effectively and efficiently translate the available scientific evidence into timely prevention-oriented action.Objectives: We applied the Navigation Guide systematic review method to answer the question “Does fetal developmental exposure to perfluorooctanoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 68 publications
7
125
0
3
Order By: Relevance
“…So werden Assoziationen zwischen PFOA-Exposition und verringertem Geburtsgewicht in den zitierten Metaanalysen sowohl für die tierexperimentellen als auch die humanepidemiologischen Studien berichtet [103][104][105]. Eine Verminderung von Markern der humoralen Immunität bei erhöhter PFAS-Belastung wurde in tierexperimentellen [106,107] und humanepidemiologischen Studien [81,83] beschrieben.…”
Section: Bekanntmachungen -Amtliche Mitteilungenunclassified
“…So werden Assoziationen zwischen PFOA-Exposition und verringertem Geburtsgewicht in den zitierten Metaanalysen sowohl für die tierexperimentellen als auch die humanepidemiologischen Studien berichtet [103][104][105]. Eine Verminderung von Markern der humoralen Immunität bei erhöhter PFAS-Belastung wurde in tierexperimentellen [106,107] und humanepidemiologischen Studien [81,83] beschrieben.…”
Section: Bekanntmachungen -Amtliche Mitteilungenunclassified
“…At that time, systematic review methodology in toxicology and chemical risk assessment was less developed than it has become more recently (see e.g. [34][35][36]), and the EviEM Executive Committee concluded that validation of the review methods would require significant efforts. One of the difficulties with the suggested review question was to define the outcome.…”
Section: Framing and Prioritisation Of Review Questionsmentioning
confidence: 99%
“…Systems for prognostic studies may start with longitudinal cohort studies as high quality of evidence (Iorio et al, 2015) or use the phase of investigation (exploratory or confirmatory study) to determine the initial level (Huguet et al, 2013). One key difference between the standard GRADE approach and the Navigation Guide systematic review methodology is that observational human studies are initially rated as moderate quality rather than as low quality (Woodruff and Sutton, 2011;Johnson et al, 2014;Koustas et al, 2014;Lam et al, 2014;.…”
Section: Evidence Grading Starting-point Adaptationsmentioning
confidence: 99%
“…The Navigation Guide methodology (Woodruff and Sutton, 2011;Johnson et al, 2014;Koustas et al, 2014;Lam et al, 2014;) applies quality-of-evidence criteria separately for human and nonhuman studies. Detailed instructions can be found here.…”
Section: Quality-of-evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation